Growing fish in recycled water: a sanitation solution? - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Many wastewater treatment plants in developing countries are either dilapidated or not functioning properly. A key reason for this underperformance is the difficulty to secure even a relatively minimal budget for operation and maintenance from those managing the plants. As a result, it has become appropriate to effectively capture the economic value of treated wastewater by generating income that can be used to help finance the operation and maintenance of wastewater treatment facilities. The production of fish in treated wastewater is an example of such an income-generating activity.